2018
DOI: 10.1007/s10616-018-0197-5
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic effects of ε-viniferin in combination with cis-platin in C6 cells

Abstract: Glioblastoma (GBM) is one of the most common and lethal forms of primary brain tumors in human adults. Treatment options are limited, and in most cases ineffective. Natural products are sources of novel compounds endowed with therapeutic properties in many human diseases like cancer. ε-viniferin is a resveratrol dimer and well known for having antiproliferative and apoptotic effects on cancer cells. Cisplatin is a platinum containing anti-cancer drug. In this study, we aimed to investigate antiproliferative an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…RES enhanced the sensitivity of these highly resistant cells to TMZ via activation of the DNA double strands/pATM/pATR/p53 pathway, leading to the activation of apoptosis. Additionally, RES promoted the differentiation of GIC involving p-STAT3 inactivation [139]. A RES dimer, ε-viniferin, has been shown to augment the apoptosis of the GBM cell line induced by another chemotherapeutic agent, cisplatin, under in vitro conditions through the activation of caspases 3, 8, and 9 [140].…”
Section: Resveratrol and Standard Anticancer Therapymentioning
confidence: 99%
“…RES enhanced the sensitivity of these highly resistant cells to TMZ via activation of the DNA double strands/pATM/pATR/p53 pathway, leading to the activation of apoptosis. Additionally, RES promoted the differentiation of GIC involving p-STAT3 inactivation [139]. A RES dimer, ε-viniferin, has been shown to augment the apoptosis of the GBM cell line induced by another chemotherapeutic agent, cisplatin, under in vitro conditions through the activation of caspases 3, 8, and 9 [140].…”
Section: Resveratrol and Standard Anticancer Therapymentioning
confidence: 99%
“…Further studies indicate that GBM-initiating cells (GICs), which display stem cell properties, are involved in tumor resistance to TMZ; RSV has been shown to enhance the sensitivity of GICs to TMZ via activation of the DNA double strands/pATM/pART/p53 pathway, inducing apoptosis [ 54 ]. Moreover, a RES dimer, ε-viniferin, has been shown to increase apoptosis of the GBM cell line, induced by cisplatin through the activation of caspase 3, 8 and 9 [ 55 ]. Another mechanism of TMZ resistance is the expression of the protein MGMT.…”
Section: Resveratrol As a Chemosensitizer Agentmentioning
confidence: 99%
“…The main results of these studies are described in Table 6 . After exposure to 100 µM for 24 h, and 95 µM and 130 µM for 48 h different cancer cells (HL-60 and C6) suffered chromatin condensation, nuclear fragmentation and contraction [ 96 , 104 ]. Thus, it seems that a prolonged exposure to this compound does not result in more damage.…”
Section: Cytotoxicity In In Vitro Studies Performed With Stilbenesmentioning
confidence: 99%
“…However, no information about the mutagenic potential of the substance was reported for this assay. In addition, more recent studies have demonstrated that ε-viniferin produces DNA damage in the A431 cell line by the comet assay [ 115 ] and the C6 cell line by the TUNEL assay [ 104 ].…”
Section: Genotoxicity In In Vitro Studies Performed With Stilbenesmentioning
confidence: 99%